Intracardiac and Intrarenal Renin-Angiotensin Systems: Mechanisms of Cardiovascular and Renal Effects. (1st November 2007) - Raizada, Veena; Skipper, Betty; Luo, Wentao; Griffith, Jeffrey
Abstract : The renin-angiotensin system (RAS) is a hormonal system that controls body fluid volume, blood pressure, and cardiovascular function in both health and disease. Various tissues, including the heart and kidneys, possess individual locally regulated RASs. In each RAS, the substrate protein angiotensinogen is cleaved by the peptidases renin and angiotensin-converting enzyme to form the biologically active product angiotensin II, which acts as an intracrine cardiac and renal hormone. The components of each RAS, including aldosterone (ALDO), may be produced locally and/or may be delivered by or sequestered from the circulation. Overactivity of the cardiac RAS has been associated with cardiac diseases, including cardiac hypertrophy due to volume and/or pressure overload, heart failure, coronary artery disease with myocardial infarction, and hypertension. Overactivity of the renal RAS has been associated with various kidney diseases, including nephropathies and renal artery stenosis. The principal effects of an overactive RAS include the generation of reactive oxygen species, which leads to "oxidative stress, " activation of the nuclear transcription factor κB, and stimulation of pathways and genes that promote vasoconstriction, endothelial dysfunction, cell hypertrophy, fibroblast proliferation, inflammation, excess extracellular matrix deposition, atherosclerosis, and thrombosis. It has been suggested that oxidative stress is the central mechanism underlying the pathogenesis of RAS-related and ALDO-related chronic cardiovascular and renal tissue injury and of cardiac arrhythmias and conduction disturbances.